2010
DOI: 10.1161/hypertensionaha.109.143339
|View full text |Cite
|
Sign up to set email alerts
|

Mononuclear Phagocyte System Depletion Blocks Interstitial Tonicity-Responsive Enhancer Binding Protein/Vascular Endothelial Growth Factor C Expression and Induces Salt-Sensitive Hypertension in Rats

Abstract: Abstract-We showed recently that mononuclear phagocyte system (MPS) cells provide a buffering mechanism for salt-sensitive hypertension by driving interstitial lymphangiogenesis, modulating interstitial Na ϩ clearance, and increasing endothelial NO synthase protein expression in response to very high dietary salt via a tonicity-responsive enhancer binding protein/vascular endothelial growth factor C regulatory mechanism. We now tested whether isotonic saline and deoxycorticosterone acetate (DOCA)-salt treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
194
1
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(210 citation statements)
references
References 24 publications
10
194
1
5
Order By: Relevance
“…It assumes isosmolarity of body fluids among the bodily compartments (2). Along with others (4-7), we (8)(9)(10)(11)(12)(13)(14) showed earlier that electrolytes are distributed in a more complex 3-compartment model, in which intravascular and the interstitial fluids do not equilibrate as readily as believed (15,16). We underscored the importance of Na + binding to negatively charged proteoglycans in the skin, the largest organ with the most extracellular space (8,11).…”
Section: Introductionsupporting
confidence: 59%
“…It assumes isosmolarity of body fluids among the bodily compartments (2). Along with others (4-7), we (8)(9)(10)(11)(12)(13)(14) showed earlier that electrolytes are distributed in a more complex 3-compartment model, in which intravascular and the interstitial fluids do not equilibrate as readily as believed (15,16). We underscored the importance of Na + binding to negatively charged proteoglycans in the skin, the largest organ with the most extracellular space (8,11).…”
Section: Introductionsupporting
confidence: 59%
“…One possible explanation is that these patients have inadequate sodium removal during HD, resulting in extracellular volume expansion and total body sodium excess (19). In vitro, increasing evidence suggests that sodium can be stored osmotically inactive in the interstitium and lead to saltsensitive hypertension (20,21). In this study and in our previous studies (2,4), we have identified slightly lower ultrafiltration volumes among patients with intradialytic hypertension; thus, sodium balance may not be adequately restored by convection alone in these patients.…”
Section: And Cd14mentioning
confidence: 37%
“…Recent work by Titze and co-workers 64 have uncovered a new system that permits buffering the effects of salt intake on the blood pressure. Sodium is bound to proteoglycans in the interstitial space under the skin, where the local hypertonicity drives an increase of the lymphatics as a consequence of the production of vascular endothelial growth factor-C by the macrophages activated by the tonicity-responsive enhancer binding protein.…”
Section: Renal Microvascular Disease and Interstitial Inflammation Armentioning
confidence: 99%